Advancements in the understanding of mechanisms of the IL-6 family in relation to metabolic-associated fatty liver disease - Liu, Jiale; Wang, Tao; Yang, Fuyuan; Pubu, Ciren (Frontiers in Endocrinology, 2025)
As lifestyle patterns change, the rates of type 2 diabetes and obesity are increasing together, leading to an increase in metabolic-associated fatty liver disease (MAFLD), now recognized as the most frequently occurring liver disease globally. MAFLD presents a significant threat to public health and imposes a substantial socioeconomic burden. This condition encompasses a spectrum of hepatic manifestations, beginning with excessive fat accumulation and hepatic steatosis, and possibly progressing to non-alcoholic steatohepatitis (NASH), liver fibrosis, cirrhosis, and liver cancer. The pathogenesis of MAFLD is intricately linked to lipid accumulation, oxidative stress, and lipotoxicity. Notably, the interleukin-6 (IL-6) cytokine family plays a complex role in the onset and development of MAFLD, primarily through the modulation of lipid metabolism, insulin resistance, inflammatory responses, and liver fibrosis. This review examines the impact of the IL-6 family on the progression of MAFLD. It explores targeting the IL-6 family as a potential future therapy for MAFLD.